PROCESS FORMATION IN THE IMPLEMENTATION OF INTEGRATED MANAGEMENT SYSTEMS IN FOOD INDUSTRY ENTERPRISES (Multidisciplinary Journal of Science and Technology, 2026)
This article provides an in-depth scientific, theoretical, and practical analysis of process formation during the implementation of Integrated Management Systems (IMS) in food industry enterprises. The advantages of an integrated approach based on international standards (ISO 9001, ISO 14001, ISO 22000, FSSC 22000, ISO 45001) are examined, along with issues related to process mapping, standardization, ensuring synergistic interactions, employee involvement, continuous improvement (PDCA/SDCA), and the integration of ESG criteria into corporate governance. Taking into account the specific safety, hygiene, environmental, and social requirements of food production, the stages of process formation, implementation challenges, and ways to improve efficiency are scientifically analyzed. The article concludes with practical recommendations applicable to the conditions of the Republic of Uzbekistan.